Performance analysis of the influence of the grid type and turbulence model on the CFD calculations - عباس, نوار (Latakia University Journal -Engineering Sciences Series, 2023)
In this research, the flow around the KVLCC2 model is calculated and analyzed using Computational Fluid Dynamics (CFD). It was focused on the flow behind the hull at the propeller plane due to its importance in determining the Propeller working conditions. Reynolds Averaged Navier Stoke method (RANS) was used to solve Navier Stokes equations, where the equations were approximated using the Finite Volumes Method (FVM). The program ANSYS was used in this research. The flow around the tanker was calculated using different grid types and different turbulence models. The resistance, velocity field at the propeller plane, and pressure distribution on the hull surface were calculated. The numerical results were compared with experimental data. This Comparison showed that the combination of the structured grid and the ????–???? ????????T turbulence model demonstrated the best results in solving the RANS equations in shipbuilding applications.